Recuperating the global migration of nurses - Mosuela, Cleovi C. (Springer International Publishing, 2020)
itting at the nexus of labor migration and health care work, this book examines the dynamic relationship between nurses' cross-border movement and efforts to regulate their migration. Grounded in multi-sited qualitative research, this volume analyzes the changing social dimensions and transnational scale of global nursing, focusing particularly on the recruitment from the Philippines to Germany. The flow of nursing skills from resource-poor countries to well-off ones is not only producing a global care crisis, but also serves as a prime example of the international race for talent and skill. As it takes a critical eye to the emerging field of migration governance or management as the preferred policy response to competing discourses of global care crises and the global competition for skilled care work, this book highlights not only the shifting web of actors, discourses, and practices in care work migration management, but also, and more importantly, how various forms of care figure in the global migration of nurses.